Bilateral Reverse Total Shoulder Arthroplasty with Soft Tissue Release for Bilateral Posterior Fracture Dislocation after Status Epilepticus. (25th March 2021) - El Rassi, George; Dib, Nabil; Maalouly, Joseph; Moukarzel, Rita; Aouad, Dany
Abstract : Proximal humerus fracture is a common orthopedic presentation, with bimodal age distribution. On the other hand, bilateral proximal humerus fracture dislocation is a rarely reported pathology, especially when it is not the result of direct trauma. We present a case of a 71-year-old female patient found to have simultaneous bilateral 4-part proximal humerus fractures following status epilepticus treated surgically with bilateral reverse shoulder arthroplasty with constraint and soft tissue release. In a patient with recurrent status epilepticus episodes, the combination of constrained reverse shoulder arthroplasty and the extensive soft tissue release should decrease the rate of failure and dislocation dramatically. We conclude, after reviewing the literature, that there is no straightforward algorithm for treating such patients and that a clear classification should take into account both bone quality and patient comorbidities which has yet to be developed.